Theoretical calculation and evaluation of n + 237, 241, 243, 245Pu reactions. (July 2020) - Guo, Hairui; Chen, Wendi; Ye, Tao; Sun, Weili; Han, Yinlu; Cai, Chonghai
Highlights: New nuclear data of n+ 237, 241, 243, 245 Pu reactions are obtained up to 150 MeV. The present results are in good agreement with the experimental data. The results make up for the lack of the data for 20 ≤ En ≤ 150 MeV. The results improve the quality of the existing nuclear data. The variation tendency of cross sections for the target isotopes is obtained. Abstract: Plutonium isotopes are important fuel or radioactive waste loaded to accelerator driven systems and some Generation-IV reactors, so accurate nuclear data of neutron induced reactions on them for the incident energy up to 150 MeV are required for the design of these facilities. The nuclear data on n + 237, 241, 243, 245 Pu reactions below 150 MeV are consistently calculated and evaluated by using the optical model, distorted wave Born approximation theory, Hauser-Feshbach theory with width fluctuation correction, fission model, evaporation model, exciton model and the intranuclear cascade model. In the meanwhile, new experimental data are taken into account. Our new evaluated data are compared with the presently existing experimental data and the evaluated data from ENDF/B-VIII, JENDL-4.0/HE and TENDL. In addition, the variation tendency of reaction cross sections related to the target mass numbers is obtained.